The infantilized researcher and research subject: ethics, consent and risk - Connor, James; Copland, Simon; Owen, Jill (Qualitative research : QR, 2018)
Current research ethics processes, based on the mantra of privacy and institutional protection, take a paternalistic approach to research participants that leaves them open to harm. Reflecting on our own research/consultancy as a case study to illustrate the current flaws, we explore our and our subjects’ experiences within the wider political context of institutional ethical rules and the Australian NHMRC guidelines. In doing so we argue for fundamental changes to the modern research ethics processes – a system that treats participants more as research collaborators rather than victims in waiting. A complete review of ethics processes is needed to empower participants and researchers to recognize the reality of the process as co-created and negotiated. This includes changes at the top level of research administration – a shift in ethics policies and procedures as well as greater education in ethics with commensurate trust for active researchers.